EXTRAMACULAR FIBROSIS IN COATS' DISEASE. Issue 10 (October 2016) - Daruich, Alejandra; Matet, Alexandre; Tran, Hoai V.; Gaillard, Marie-Claire; Munier, Francis L.
Abstract : Purpose: To determine the rate, risk factors, and outcome of extramacular fibrosis in Coats' disease. Methods: Consecutive cases from a single center were retrospectively reviewed. Clinical characteristics and treatments were analyzed by comparative, multivariate, and survival approaches. Results: Among 69 patients with Coats' disease, 28 (40.6%) showed evidence of extramacular fibrosis (mean follow-up: 58.2 months). Mean time of fibrosis onset was 17.4 months. Extent of retinal exudation and rate of exudative retinal detachment at baseline were significantly higher in eyes that developed extramacular fibrosis compared with those that did not ( P < 0.001). Similarly, these parameters showed significant differences using multivariate ( P < 0.05) and survival analysis ( P < 0.001). Extension of telangiectasia, number of cryotherapy, or laser sessions, and treatment by anti-vascular endothelial growth factor were not associated with extramacular fibrosis. Final visual acuity was worse in patients with extramacular fibrosis ( P < 0.001). The rates of tractional retinal detachment and macular fibrosis were higher in patients with extramacular fibrosis (39%.0 vs. 0% and 60.7% vs. 19.5%, respectively, P < 0.001). Conclusion: Extramacular fibrosis led to a worse visual prognosis and was associated with the extension of retinal exudation and the presence of exudative retinal detachment at diagnosis. Treatment should target a quick resolution of exudation to limit its development. Abstract : Among 69 patients with Coats' disease, extramacular fibrosis was detected in 28 cases (40.6%) over a mean of 58 months. Its development was associated with the extension of retinal exudation ( P < 0.001) and the presence of exudative retinal detachment ( P < 0.001) at baseline. Final visual acuity was worse in these eyes ( P < 0.001).